Submicron soft-magnetic particulate and method of producing the same, and soft-magnetic body material and soft-magnetic body containing submicron soft-magnetic particulate

JP2025035886APending Publication Date: 2025-03-14TOHOKU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023143208
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0008】 本発明は、Fe、Fe以外の金属M及びBを構成元素とするサブミクロンサイズの平均粒子径を有し、磁気特性に優れた軟磁性微粒子と、その製造方法とを提供できる。また、本発明は、優れた磁気特性を示す軟磁性微粒子を用いた軟磁性材料及び軟磁性体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035886000001_ABST
    Figure 2025035886000001_ABST
Patent Text Reader

Abstract

To provide a soft-magnetic particulate excellent in magnetic properties containing Fe, metal M other than Fe, and B as constituent elements and having a submicron-sized average particle diameter, a soft-magnetic body material and a soft-magnetic body using the soft-magnetic particulate, and a method of producing the soft-magnetic particulate.SOLUTION: Provided are a submicron soft-magnetic particulate contains Fe, metal M other than Fe, and B; a soft-magnetic body material and a soft-magnetic body containing the submicron soft-magnetic particulate; and a method of producing a submicron soft-magnetic particulate including mixing a metal salt solution containing Fe salt, metal salt other than Fe salt and a complexing agent and having a pH of 13 or greater with a reducer solution containing a B-based reducer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to sub-micron soft magnetic particles and a method for producing the same, as well as a soft magnetic material and a soft magnetic body containing the sub-micron soft magnetic particles. [Background technology]

[0002] Magnetic particles have different magnetic properties depending on their size, so they are used for applications that depend on the magnetic properties they exhibit. For example, submicron-sized magnetic particles are used as materials for power electronics devices such as magnetic binders and inductors for ultra-high frequency bands of 1 MHz or more, as well as electromagnetic wave absorbers (noise suppressors) and antennas, and other electronic devices that operate with electromagnetic waves. In particular, submicron-sized magnetic particles are expected to be used as materials for high-frequency devices that operate at frequencies from tens of MHz to several GHz, because they can suppress eddy current losses and shift the resonance frequency to higher frequencies. As magnetic fine particles, for example, Patent Document 1 describes "amorphous soft magnetic alloy powder consisting of particles formed from an aggregate of two or more fine particles having a particle size of 0.01 μm to 1.0 μm and a single particle formed from only one particle, characterized in that the average particle size of the entire produced powder is 0.1 μm to 5.0 μm, 5 wt%≦B≦10 wt%, 0.06 wt%≦P≦5 wt%, and the remainder is Fe." In addition, Patent Document 1 describes a method for producing soft magnetic fine particles, in which a reducing solution containing a B-based reducing agent is added dropwise while stirring a raw material solution containing an iron salt, a complexing agent, a pH adjuster, a dispersant, and a P-based reducing agent and adjusted to a pH range of 9 to 10. [Prior art documents] [Patent documents]

[0003] [Non-Patent Document 1] Patent No. 5382923 Summary of the Invention [Problem to be solved by the invention]

[0004] As a method for producing fine particles, the atomization method, the carbonyl decomposition method, the spray pyrolysis method, etc. are known. These production methods can usually produce fine particles of micron size or more, but cannot produce fine particles of submicron size. On the other hand, the aqueous solution reduction reaction method, in which metal ions and the like are reduced in a state in which they are liberated in water to precipitate metal fine particles, can produce fine particles of submicron size, but the fine particles are prone to agglomeration during the production process, and aggregates (secondary particles) with rough surfaces and large particle diameters are also formed. For example, as described in Patent Document 1, the "amorphous soft magnetic alloy powder" of Patent Document 1 produced by the aqueous solution reduction reaction method also contains "particles formed from an aggregate of two or more fine particles". Therefore, even in the conventional aqueous solution reduction reaction method, it is often impossible to suppress agglomeration during production (reaction), and an aggregate of fine particles of submicron size cannot be produced. In recent years, the performance of power electronics devices and electronic devices has been rapidly improved, and accordingly, submicron particles with even better magnetic properties are desired. However, when multiple metal elements that serve as the base of the particles are used in combination to alloy the particles in hopes of improving the magnetic properties, the behavior of the metal ions in the aqueous solution in the aqueous solution reduction reaction method cannot be controlled, making it even more difficult to manufacture submicron-sized particles. As described above, there is a demand for magnetic fine particles to have a particle size of submicron size by suppressing the formation of aggregates, and to further improve the magnetic properties. However, Patent Document 1 does not consider at all the suppression of the formation of aggregates, nor further the improvement of the magnetic properties.

[0005] The present invention aims to provide soft magnetic particles having a submicron average particle size and excellent magnetic properties, and containing Fe, a metal other than Fe, M, and B as constituent elements, and a method for producing the same. Another objective of the present invention is to provide a soft magnetic material and a soft magnetic body using the soft magnetic particles exhibiting excellent magnetic properties. [Means for solving the problem]

[0006] The present inventors have conducted intensive studies in view of the above problems, and have found that, in an aqueous solution reduction reaction method, when the pH of an aqueous metal salt solution containing an Fe salt, a metal salt other than an Fe salt, and a complexing agent is set to 13 or more, and then an aqueous reducing agent solution containing a B-based reducing agent is mixed, the aggregation of fine particles generated during production can be suppressed, and metal fine particles having a submicron particle size and containing Fe, a metal M other than Fe, and B as constituent elements can be produced. Furthermore, the present inventors have also found that the produced metal fine particles have Fe and a metal M other than Fe as constituent elements and have a submicron average particle size, and therefore exhibit excellent soft magnetic properties and can be suitably used as a soft magnetic material for power electronics devices and the above-mentioned electronic devices. The present invention has been completed through further studies based on these findings.

[0007] The object of the present invention has been achieved by the following means. <1> Submicron soft magnetic particles containing Fe, metals other than Fe, and B. <2> The metal M includes at least one selected from Ni, Co, Zn, Al, Mn, and Cr; <1> 2. The submicron soft magnetic particles according to claim 1. <3> The Fe content C Fe (atm%) and the content C of the metal M M (atm%) and the content ratio [C Fe :C M ] is 3:7~8:2. <1> or <2> 2. The submicron soft magnetic particles according to claim 1. <4> A method for producing submicron soft magnetic particles containing Fe, a metal other than Fe, M, and B, comprising the steps of: A manufacturing method comprising mixing an aqueous solution of a metal salt containing an Fe salt, a metal salt other than an Fe salt, and a complexing agent and having a pH of 13 or more with an aqueous solution of a reducing agent containing a B-based reducing agent. <5> The mixing is carried out under non-heating conditions. <4> The manufacturing method described in <6> the complexing agent comprises glycine; <4> or <5> The manufacturing method described in <7> heat treating the fine particles obtained by the mixing; <4> ~ <6> The method for producing a product according to any one of claims 1 to 5. <8> the above <1> ~ <3> 13. A soft magnetic material comprising the submicron soft magnetic particles according to any one of claims 1 to 12. <9> the above <1> ~ <3> 13. A soft magnetic material comprising the submicron soft magnetic particles according to any one of claims 1 to 12. Effect of the Invention

[0008] The present invention can provide soft magnetic particles having a submicron average particle size and excellent magnetic properties, and containing Fe, a metal other than Fe, M, and B as constituent elements, and a method for producing the same. The present invention can also provide soft magnetic materials and soft magnetic bodies using the soft magnetic particles exhibiting excellent magnetic properties. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is an image of the submicron soft magnetic particles produced in Example 1 taken with a scanning electron microscope. [Diagram 2] FIG. 2 is a graph showing the particle size distribution of the submicron soft magnetic particles produced in Example 1. [Diagram 3] FIG. 3 is an image showing a halo pattern obtained by electron beam analysis of the submicron soft magnetic particles produced in Example 1. [Figure 4] FIG. 4 is a graph showing the results of measuring the complex permeability of the submicron soft magnetic particles produced in Example 1. [Diagram 5] FIG. 5 is a graph showing the results of the static magnetic properties of each of the submicron soft magnetic particles produced in Example 2. [Figure 6] FIG. 6 is a graph showing the results of the dynamic magnetic properties of each of the submicron soft magnetic particles produced in Example 2. [Figure 7] FIG. 7 is a diagram showing images taken by a scanning electron microscope of each of the submicron soft magnetic particles produced in Example 2, as well as the results of the Fe:Ni content ratio [Fe:Ni] and average particle size. [Figure 8] FIG. 8 is an image of each of the submicron soft magnetic particles produced in Example 4 taken with a scanning electron microscope. [Figure 9]FIG. 9 is a graph showing the results of measuring the saturation magnetization of each of the submicron soft magnetic particles produced in Example 3 and Example 4. [Figure 10] FIG. 10 is a graph showing the results of measuring the coercive force of each of the submicron soft magnetic particles produced in Examples 3 and 4. [Figure 11] FIG. 11 is a graph showing the results of the dynamic magnetic properties of each of the submicron soft magnetic particles produced in Example 4. [Figure 12] FIG. 12 is a graph showing the particle size distribution of the submicron soft magnetic particles produced in Example 5. [Figure 13] FIG. 13 is an image of the submicron soft magnetic particles produced in Comparative Example 1 taken with a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the present invention and this specification, a numerical range expressed using "to" means a range including the numerical values ​​written before and after "to" as the lower and upper limits. In this specification, when multiple numerical ranges are set stepwise for the content of a component, physical properties, etc., the upper and lower limits forming the numerical range can be appropriately combined.

[0011] [Submicron soft magnetic particles] The submicron soft magnetic fine particles of the present invention (hereinafter simply referred to as "soft magnetic fine particles of the present invention") are alloy fine particles containing Fe, metals other than Fe, M and B as constituent elements, and have an average particle size of submicron size.

[0012] The elements constituting the soft magnetic fine particles of the present invention include Fe, metals other than Fe, M and B, and may also contain other elements. The metal M other than Fe may be any metal element that is ionized in a metal salt aqueous solution in the method for producing submicron soft magnetic particles (aqueous solution reduction reaction method) described later, precipitates together with Fe through reduction reaction, and forms an alloy, and may include various metal elements. For example, metal elements belonging to groups 1 to 14 in the periodic table of elements may be included, and among these, transition metal elements belonging to groups 3 to 13 are preferred, metal elements selected from Ni, Co, Zn, Al, Cr, and Mn are more preferred, and magnetic elements other than Fe, such as Ni, Co, Mn, and Cr, are even more preferred in terms of magnetic properties. The metal M other than Fe may be one type, or two or more types. The other elements are elements that do not fall under any of Fe, metal M, and B, and examples thereof include metalloid elements other than B. The number of other elements may be one or more.

[0013] In the soft magnetic particles of the present invention, the content (atm%) of each element can be appropriately set in consideration of the magnetic properties, etc. For example, the content C of Fe is Fe The content C of the metal M can be set to 20 to 65 atm%, and is preferably set to 30 to 65 atm% in order to obtain soft magnetic properties with a high saturation magnetic flux density. M The content C of B can be set to 20 to 65 atm%, and is preferably set to 20 to 55 atm% in order to freely select a high saturation magnetic flux density or a high magnetic permeability. B The content of other elements C can be set to 15 to 35 atm%, and is preferably set to 15 to 25 atm% in order to prevent deterioration of magnetic properties. A (atm%) is not particularly limited and can be set appropriately. The content of each element is selected within the above range so that the total content of each element is 100 atm%. When the soft magnetic particles contain two or more kinds of metal M and / or other elements, the above content of each element is the total content. The content (atm %) of each element can be determined by the method described in the Examples below.

[0014] In the soft magnetic particles of the present invention, the Fe content C Fe(atm%) and metal M content C M (atm%) and the content ratio [C Fe :C M The content ratio [C Fe :C M ] can be, for example, 3:7 to 9:1, preferably 3:7 to 8:2 in terms of magnetic properties, and more preferably 4:6 to 6:4 in terms of achieving excellent complex permeability.

[0015] The soft magnetic particles of the present invention have an average particle size of submicron size. In the present invention, the average particle size of submicron size means that the average particle size measured by the measurement method in the examples described later is 100 nm or more and 1.5 μm or less, preferably 1 μm or less. The average particle size is also referred to as the median diameter (D 50 ) The median diameter means the particle diameter at which the particle size distribution is measured by a measurement method in the Examples described later, and the cumulative distribution is 50% when the total volume of the particles is 100%. In the present invention, the average particle diameter means the average particle diameter of the entire soft magnetic microparticles of the present invention, but since the soft magnetic microparticles of the present invention are an aggregate of a plurality of primary particles as described later, it approximately coincides with the average particle diameter of the primary particles (average primary particle diameter). The average particle size of the soft magnetic fine particles of the present invention can usually be 100 to 1500 nm, preferably 150 to 750 nm, and more preferably 200 to 600 nm. When the average particle size is in the above range, the soft magnetic fine particles have excellent magnetic properties, particularly complex permeability. The average particle size is determined by the Fe content C Fe It tends to become larger when

[0016] As shown in the examples below, the soft magnetic particles of the present invention are aggregates of a plurality of independently existing (dispersed) spherical primary particles, and have an amorphous structure or a microcrystalline structure. As shown in the examples below, the soft magnetic particles of the present invention are aggregates of non-aggregated particles with a smooth surface shape and uniform particle size, and have a narrow particle size distribution. It is considered that such soft magnetic particles of the present invention are not aggregate particles formed by the growth of nuclei during the manufacturing process, but multiple primary particles with uniform particle size are formed by particle growth such as the LaMer mechanism. In the present invention, the particles being "spherical" are not limited to particles that are truly spherical, but include particles that are recognized as being approximately spherical in an image observed during measurement of the average particle size. In the present invention, even in the soft magnetic fine particles that have been subjected to the heat treatment described below, the above-mentioned aggregate of primary particles and the amorphous structure or microcrystalline structure are maintained.

[0017] The soft magnetic particles of the present invention have an average particle size of submicron size composed of the above-mentioned constituent elements, and therefore exhibit excellent magnetic properties. The magnetic properties exhibited by the soft magnetic particles of the present invention are not unique, and are characteristics that depend on the content, type and number of the constituent elements, and further on the average particle size. For example, the Fe content C Fe When increasing the saturation magnetization σ S (mass magnetization) becomes higher, and the coercive force H C Specifically, this is as shown in the examples described later. It consists of Fe, Ni and B, and the Fe content is C Fe and Ni content C Ni The content ratio [C Fe :C Ni For example, for a submicron soft magnetic particle with a saturation magnetization of σ S (at room temperature) is 74.6 emu / g or more, and the coercive force H C exhibits static magnetic properties of 50 Oe or less, and exhibits dynamic magnetic properties in which the real part μ' of the complex permeability is 1.5 or more, and the rise time (tan δ) of the imaginary part μ'' is 0.5 GHz or more. The soft magnetic particles of the present invention maintain or improve their excellent static magnetic properties after the heat treatment described below, while their dynamic magnetic properties are further improved. In the case of submicron soft magnetic particles (after heat treatment) made of Fe, Ni and B, the saturation magnetization σ S becomes higher, and the coercive force H C tends to be lower, the real part μ' of the complex permeability tends to be higher, and the rising edge of the imaginary part μ'' tends to shift to a high frequency band of 1 GHz or higher.

[0018] The composition, structure, average particle size, magnetic properties, etc. of the soft magnetic microparticles of the present invention can be identified and qualified by known analytical methods such as observation with a scanning electron microscope, inductively coupled plasma (ICP) mass spectrometry, electron beam analysis, X-ray powder diffraction (XRD), thermogravimetry-differential thermal analysis (TG-DTA), X-ray fluorescence spectroscopy (XRF), vibrating sample magnetometer (VSM), complex permeability measurement, etc., specifically, by the methods and conditions in the examples described below.

[0019] [Soft magnetic material] The soft magnetic fine particles of the present invention exhibit excellent soft magnetic properties and can therefore be suitably used as a material for forming a soft magnetic body (referred to as a "soft magnetic body material" in the present invention). The soft magnetic material of the present invention only needs to contain the soft magnetic fine particles of the present invention, and may contain resin, elastomer, nonwoven fabric, etc. depending on the application of the soft magnetic material to be formed. The components fu of the soft magnetic fine particles, resin, etc. contained in the soft magnetic material may each be one type or two or more types. The soft magnetic material of the present invention is preferably a resin composition containing the soft magnetic microparticles of the present invention and a resin, which exhibits excellent moldability and can be used as a soft magnetic material for various applications, and which expresses the magnetic properties of the soft magnetic microparticles of the present invention.

[0020] The resin contained in the soft magnetic material is not particularly limited, and may be any of various thermoplastic resins and thermosetting resins. Examples of the resin include epoxy resin, phenol resin, silicone resin, polyamideimide resin, unsaturated polyester resin, diallyl phthalate resin, xylene resin, polyester resin, polyvinyl chloride resin, polyvinyl butyral resin, polyurethane resin, and cellulose resin. The elastomer contained in the soft magnetic material is not particularly limited, and may be any of nitrile-butadiene rubber, styrene-butadiene rubber, and styrene-butadiene rubber. The nonwoven fabric contained in the soft magnetic material is not particularly limited, and may be any of polyester, polypropylene, polyethylene, rayon, and nylon.

[0021] The content of each component in the soft magnetic material is appropriately determined depending on the application, required properties, etc. of the soft magnetic material. For example, the content of the soft magnetic fine particles of the present invention in the soft magnetic material can be 10 to 70% by mass, and the total content of the resin and elastomer in the soft magnetic material can be 30 to 90% by mass. The soft magnetic material of the present invention can be prepared by mixing the soft magnetic fine particles of the present invention, a resin, an elastomer or a nonwoven fabric, and further appropriate components.

[0022] [Soft magnetic material] The soft magnetic material of the present invention may be any material containing the soft magnetic fine particles of the present invention, and may be the soft magnetic fine particles of the present invention themselves, but is usually a molded product obtained by molding the soft magnetic material of the present invention into a desired shape and size depending on the application, etc. The shape of the soft magnetic material of the present invention may be, for example, a long sheet, a single sheet, a rectangular parallelepiped shape, a cylindrical shape, a ring core shape, or any other shape. As the molding method, various known molding methods can be applied without any particular limitation. The soft magnetic body of the present invention may have other members, such as a base sheet or a molded body case. The soft magnetic material of the present invention can be used in various applications that utilize soft magnetic properties, and can be suitably used, for example, in power electronics devices such as magnetic binders and inductors for ultra-high frequency bands of 1 MHz or more, electromagnetic wave absorbers (noise suppressors), antennas, and other electronic devices that operate with electromagnetic waves. In particular, by utilizing high dynamic magnetic properties while maintaining excellent static magnetic properties, the material can be suitably used in high frequency devices that operate at several tens of MHz to several GHz.

[0023] [Method of manufacturing submicron soft magnetic particles] The method for producing submicron soft magnetic particles of the present invention (hereinafter sometimes simply referred to as "the production method of the present invention") is a production method that includes mixing an aqueous reducing agent solution containing a B-based reducing agent with an aqueous metal salt solution containing an Fe salt, a metal salt other than an Fe salt, and a complexing agent and having a pH of 13 or more, and can produce the submicron soft magnetic particles of the present invention that exhibit the above-mentioned excellent magnetic properties, as well as properties such as average particle size and structure. In particular, the production method of the present invention can produce soft magnetic particles having an average particle size of submicron size even under non-heating conditions where conventional aqueous solution reduction reaction methods cannot produce submicron particles.

[0024] <Metal salt aqueous solution> The aqueous metal salt solution used in the production method of the present invention is an aqueous solution containing an Fe salt, a metal salt other than an Fe salt, and a complexing agent. As the water, well water, tap water, etc. can be used, but it is preferable to use distilled water, purified water, pure water, etc. The Fe salt is not particularly limited, and examples thereof include inorganic salts and organic salts of Fe, such as iron sulfate (II), iron chloride (II), iron chloride (III), iron sulfate (III), iron acetate (II), iron oxalate (II), etc. The Fe salt may be anhydrous or hydrated. Metal salts other than Fe salts are not particularly limited, and include inorganic salts and organic salts of metal M other than Fe described above. For example, Ni salts include nickel sulfate, nickel chloride, nickel nitrate, nickel fluoride, nickel acetate, nickel oxalate, nickel carbonate, etc. Co salts include cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt carbonate, etc. Zn salts include zinc sulfate, zinc chloride, zinc nitrate, zinc fluoride, zinc acetate, zinc oxalate, zinc carbonate, etc. Al salts include aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum fluoride, aluminum acetate, aluminum oxalate, aluminum carbonate, etc. Mn salts include manganese sulfate, manganese chloride, manganese nitrate, manganese fluoride, manganese acetate, manganese oxalate, manganese carbonate, etc. Cr salts include chromium sulfate, chromium chloride, chromium nitrate, chromium fluoride, chromium acetate, chromium oxalate, chromium carbonate, etc. Examples of the salts of metals M other than the above include sulfates, chlorides, nitrates, fluorides, acetates, oxalates, carbonates, etc. of metals M other than the above. Metal salts other than Fe salts may be anhydrides or hydrates. When the soft magnetic particles to be produced contain the above-mentioned other elements, the metal salt aqueous solution further contains a salt of the other elements. The salt of the other elements is not particularly limited, and examples thereof include sulfates, chlorides, nitrates, fluorides, acetates, oxalates, carbonates, etc. of the other elements. The salt of the other elements may be anhydrides or hydrates.

[0025] The complexing agent is not particularly limited, and various complexing agents that can be applied to the aqueous solution reduction reaction method can be used, such as glycine, alanine, ammonium sulfate, ammonium chloride, and trisodium citrate. Among them, α-amino acids such as glycine and alanine are preferred, and glycine is more preferred in that it allows efficient production of submicron soft magnetic particles that are inhibited from being burned by alkali.

[0026] The aqueous metal salt solution may contain a dispersant, a catalyst, an antifoaming agent, a reducing agent other than the B-type reducing agent, and the like.

[0027] The content of each component in the aqueous metal salt solution is appropriately determined depending on the composition of the soft magnetic fine particles to be produced, the amount of B-based reducing agent mixed, and the like. For example, the content of the Fe salt in the metal salt aqueous solution may be 0.05 to 0.7 mol / L. The content of the metal salt other than the Fe salt in the metal salt aqueous solution may be 0.05 to 0.7 mol / L. The content ratio of the Fe salt content (mol / L) to the content (mol / L) of the metal salt other than the Fe salt in the metal salt aqueous solution [content of Fe salt: content of the metal salt other than the Fe salt] is not particularly limited, but in the manufacturing method of the present invention, the above content ratio [C Fe :C M ], so this content ratio [C Fe :C M It is preferable to set the content of the Fe salt in the metal salt aqueous solution to the same range as that of the Fe salt in the metal salt aqueous solution. When the content of the Fe salt in the metal salt aqueous solution is increased, the average particle size of the soft magnetic microparticles produced tends to increase, and when the content of the metal salt other than the Fe salt in the metal salt aqueous solution is increased, the average particle size of the soft magnetic microparticles produced tends to decrease. The content of the salt of the other element is not particularly limited and can be set appropriately. When the metal salt aqueous solution contains two or more kinds of Fe salt, metal salt other than Fe salt, and / or salt of the other element, the above content is the total content. The content of the complexing agent in the aqueous metal salt solution is appropriately determined taking into consideration the content of the Fe salt and the content of the metal salt other than the Fe salt, and can be 0.25 to 4.0 times by mole, and preferably 0.5 to 2.0 times by mole, the total amount of the content (mol) of the Fe salt and the content (mol) of the metal salt other than the Fe salt.

[0028] The pH of the metal salt aqueous solution (before mixing with the reducing agent aqueous solution) is set to 13 or more. This suppresses the precipitation of (complex) ions of Fe and metal M, and provides a predetermined alloy composition (content ratio [C Fe :C MThat is, when the pH of the metal salt aqueous solution is set to 9 to 10 as in the conventional aqueous solution reduction reaction method described in Patent Document 1, the preferential and excessive precipitation of metal M in particular cannot be suppressed, and the content C of metal M in the obtained fine particles becomes high. M In addition, the amount of metal becomes too large, and aggregated particles are also likely to be generated. In the present invention, the reason why submicron-sized soft magnetic particles having a specified alloy composition can be produced when the pH of the metal salt aqueous solution is set to 13 or more is not yet clear, but it is thought that hydroxide ions (complex ions) of metal M are generated in the metal salt aqueous solution, and the complexing power of these ions can suppress preferential and excessive precipitation of metal M ions. In addition, it is thought that by setting the pH of the metal salt aqueous solution to 13 or more, the generated metal hydroxide dissolves in the aqueous solution and reduces the viscosity, making it easier to stir, and thus suppressing aggregation. In the production method of the present invention, the pH of the metal salt aqueous solution is preferably 13.5 or higher, from the viewpoint of efficiently (highly yielding) producing submicron-sized soft magnetic fine particles having a specific alloy composition. As described above, the manufacturing method of the present invention in which the pH of the metal salt aqueous solution is 13 or more can manufacture submicron-sized soft magnetic fine particles having a predetermined alloy composition corresponding to the content ratio of the Fe salt and the metal salt other than the Fe salt in the metal salt aqueous solution. Therefore, by changing the content ratio of the Fe salt and the metal salt other than the Fe salt in the metal salt aqueous solution, any alloy composition (content ratio [C Fe :C M ]) can be easily produced. The pH of the aqueous metal salt solution can be adjusted with a pH adjuster such as sodium hydroxide, aqueous ammonia, or sodium hydrogen carbonate.

[0029] The aqueous metal salt solution can be prepared by dissolving an Fe salt, a metal salt other than an Fe salt, a complexing agent, and further any optional components in water, and preferably generating complex ions of Fe and metal M. The preparation can usually be carried out under non-heating conditions, but can also be carried out under heating conditions to promote dissolution of the components or generation of complex ions. In the production method of the present invention, when the pH of the prepared metal salt aqueous solution is less than 13, a pH adjuster is added to adjust the pH of the metal salt aqueous solution to at least 13. When the pH of the prepared metal salt aqueous solution is at least 13, there is no need to adjust the pH.

[0030] <Reducing agent aqueous solution> The aqueous reducing agent solution used in the production method of the present invention is an aqueous solution containing a B-type reducing agent. As the water, well water, tap water, etc. can be used, but it is preferable to use distilled water, purified water, pure water, etc. The B-based reducing agent is not particularly limited as long as it is a reducing agent containing B, and examples thereof include sodium borohydride, potassium borohydride, and dimethylaminoborane. The aqueous reducing agent solution may contain a P-based reducing agent such as sodium hypophosphite or calcium hypophosphite, or hydrazine as a reducing agent other than the B-based reducing agent.

[0031] The content of each component in the reducing agent aqueous solution is appropriately determined depending on the composition of the soft magnetic fine particles to be produced, the mixed amount of various metal salts in the metal salt aqueous solution, etc. For example, the content of the B-based reducing agent in the reducing agent aqueous solution can be set within the range of 0.3 to 1.2 mol / L, taking into account the mixing ratio described later.

[0032] The aqueous solution of the reducing agent can be prepared by dissolving the B-type reducing agent and any other components in water. The preparation can usually be carried out under non-heating conditions, but can also be carried out under heating conditions to promote dissolution of the components. The pH of the prepared reducing agent aqueous solution (before mixing with the metal salt aqueous solution) is not particularly limited, but is usually alkaline. If necessary, the pH of the reducing agent aqueous solution can be appropriately adjusted using the above-mentioned pH adjuster.

[0033] <Mixing of metal salt aqueous solution and reducing agent aqueous solution> In the manufacturing method of the present invention, a reducing agent aqueous solution is mixed with a metal salt aqueous solution having a pH of 13 or more. This reduces metal ions in the metal salt aqueous solution and causes them to precipitate as submicron-sized alloy particles. The mixing conditions (reduction reaction conditions) are not particularly limited and can be determined appropriately. For example, the mixing temperature can be -10 to 90°C, but as described above, non-heating conditions that cannot be applied in the conventional aqueous solution reduction reaction method can be applied, and cooling conditions can also be applied. The mixing temperature is preferably in the range of -10 to 40°C, more preferably 0 to 15°C, in terms of being able to produce the soft magnetic fine particles of the present invention easily and with good workability. The method of mixing the metal salt aqueous solution and the reducing agent aqueous solution is preferably to drop the reducing agent aqueous solution into the metal salt aqueous solution. The dropping speed at this time cannot be uniquely determined depending on the production scale, but can be, for example, 100 to 5000 mL / h if the total amount of the metal salt aqueous solution and the reducing agent aqueous solution is up to a scale of several liters. During the mixing of the metal salt aqueous solution and the reducing agent aqueous solution, the metal salt aqueous solution and the reaction system (mixed solution) are preferably stirred and / or irradiated with ultrasonic waves. The stirring speed cannot be uniquely determined depending on the production scale, and is determined appropriately. The mixing time (reaction time) is appropriately determined taking into consideration the progress of the reduction reaction, and can be, for example, 0.5 to 2.0 hours (including the dropwise addition time). The amount of the metal salt aqueous solution and the reducing agent aqueous solution mixed may be an amount capable of reducing Fe ions and metal Mno ions in the metal salt aqueous solution, and may be, for example, 0.5 to 3.0 times by mole, and preferably 1.0 to 2.0 times by mole, the total amount of the Fe ion content (mol) and the metal M ion content (mol) in the metal salt aqueous solution.

[0034] In the production method of the present invention, the pH of the metal salt aqueous solution may be 13 or higher when the metal salt aqueous solution and the reducing agent aqueous solution start to be mixed, but it is preferable that the pH of the mixed system is maintained at 13 or higher during and until the mixing is completed (completion of the reduction reaction), and the pH of the mixed system can also be appropriately adjusted to 13 or higher using the above-mentioned pH adjuster.

[0035] In the production method of the present invention, conditions other than the pH of the metal salt aqueous solution, the mixing method and the mixing apparatus can be appropriately set or selected by referring to known aqueous solution reduction reaction methods, for example, The Papers of Tech. Meeting Magn., IEEJ, MAG-19-080, 7-11 (2019), etc. In the manufacturing method of the present invention, the soft magnetic particles obtained by mixing the aqueous metal salt solution and the aqueous reducing agent solution as described above are collected by filtration or the like, and then appropriately washed and dried to produce the desired submicron soft magnetic particles of the present invention. The obtained submicron soft magnetic particles exhibit excellent magnetic properties, etc., as described above.

[0036] <Heat treatment (annealing)> In the manufacturing method of the present invention, the submicron soft magnetic particles obtained by the above mixing (sometimes referred to as "submicron soft magnetic particles before heat treatment" in the present invention) can be heat-treated to further improve the magnetic properties, particularly the dynamic magnetic properties, of the submicron soft magnetic particles obtained by the above mixing. The reason why heat-treating the submicron soft magnetic particles obtained by mixing can further improve, particularly the dynamic magnetic properties, is not yet clear, but one possible reason is thought to be that the internal distortion of the submicron soft magnetic particles before heat treatment is eliminated. The heat treatment conditions are not particularly limited and can be set appropriately. For example, the heat treatment temperature can be set within a range including the peak temperature observed by differential thermal analysis (DTA) of the submicron soft magnetic fine particles before the heat treatment, specifically, 350 to 550°C, preferably 400 to 500°C. The heating time can usually be 15 minutes to 2 hours after the predetermined heating temperature is reached. The heating rate and pressure in the heat treatment can be set appropriately. The heat treatment can be carried out on the submicron soft magnetic fine particles as they are before the heat treatment, or on a mixture of the submicron soft magnetic fine particles before the heat treatment and the above-mentioned resin or a molded product thereof.

[0037] In the manufacturing method of the present invention, the submicron soft magnetic particles before heat treatment are heat-treated and then cooled to produce the desired submicron soft magnetic particles of the present invention. The obtained submicron soft magnetic particles exhibit particularly excellent dynamic magnetic properties as described above. When the heat treatment is performed on the mixture or a molded product thereof, a soft magnetic material and a soft magnetic body containing submicron soft magnetic particles exhibiting particularly excellent dynamic magnetic properties are produced. EXAMPLES

[0038] The present invention will be described in more detail with reference to the following examples. The present invention is not to be construed as being limited to the following examples except as defined in the present invention.

[0039] [Example 1] <Preparation of metal salt aqueous solution> In a glass beaker, 10 g (0.17959 mol / L) of iron (II) sulfate heptahydrate, 9.45 g (0.17959 mol / L) of nickel sulfate hexahydrate, and 5.4 g (0.3597 mol / L, 1.0 times the molar ratio of the total content of Fe and Ni) of glycine were added together with 200 mL of distilled water, and the mixture was stirred at room temperature (25°C) with a stirrer (80 rpm) until each component was dissolved. Sodium hydroxide was added to the resulting aqueous solution to adjust the pH to 13.5, preparing an aqueous metal salt solution. <Preparation of reducing agent aqueous solution> Into a glass beaker, 5.4 g (0.7135 mol / L) of sodium borohydride was placed together with 200 mL of distilled water, and the mixture was stirred at room temperature (25° C.) with a stirrer (stirring speed: 80 rpm) to prepare an aqueous reducing agent solution.

[0040] <Mixed> The metal salt aqueous solution and the reducing agent aqueous solution were each cooled to 0°C. In a nitrogen atmosphere, the entire amount of the aqueous reducing agent solution (internal temperature 0°C, the mixed amount of sodium borohydride relative to the total content of Fe content and Ni content was 1.98 times in molar ratio) was dropped at a dropwise rate of 200 mL / L into the entire amount of the aqueous metal salt solution (internal temperature 0°C) being stirred with a stirrer (stirring speed 80 rpm), and the mixed solution was stirred for 90 minutes, including the dropwise addition time, while continuing stirring. After stirring for 90 minutes, foaming from the mixture ceased and the reduction reaction was completed. After stirring for 90 minutes, the precipitated fine particles were collected by filtration, washed with distilled water, substituted with alcohol, and dried in an inert atmosphere of nitrogen gas, to obtain submicron soft magnetic fine particles of Example 1.

[0041] The submicron soft magnetic particles of Example 1 thus produced were identified and evaluated in terms of composition, structure, magnetic properties, etc., as follows. <Composition> The composition of the submicron soft magnetic particles of Example 1 was identified by the following method and conditions. 34.3 Ni 41.0 B 24.7 (The content of each atom is atm%), and the content ratio of Fe and Ni [C Fe :C Ni ] was 4.6:5.4. (Method and Conditions) The Fe and Ni content ratios in the submicron soft magnetic particles were measured using a scanning electron microscope (FE-SEM (EDX), JSM-6500F, manufactured by JEOL Ltd.). The Fe, Ni and B contents in the submicron soft magnetic particles were also measured using an inductively coupled plasma (ICP) mass spectrometer (Agilent 8800).

[0042] <Average particle size> The submicron soft magnetic particles of Example 1 were photographed using a scanning electron microscope (observation magnification: 30,000 times), and the longest diameter of all particles within the photographed field of view was measured using image processing software ImageJ to determine the particle size distribution. The image photographed with the scanning electron microscope is shown in Figure 1, and the particle size distribution is shown in Figure 2. As a result, as shown in Figure 1, the particles were an aggregate of spherical primary particles (non-aggregating) with an average particle diameter D 50 The particle diameter was 204 nm, and as shown in FIG. 2, the particle diameter distribution was narrow and uniform.

[0043] <Crystal structure> The submicron soft magnetic particles of Example 1 were observed at a magnification of 50,000 times using a transmission electron microscope (JEM-2100, manufactured by JEOL Ltd.) and subjected to electron beam analysis. As shown in Figure 3, a halo pattern was confirmed, indicating that the particles had an amorphous structure. When the crystallization temperature of the submicron soft magnetic particles of Example 1 was measured using a simultaneous differential thermal and thermogravimetric analyzer (TG-DTA, EXSTAR-6000 TG / DTA6300 (product name, model number), manufactured by Seiko Instruments (SII) Inc.), peaks were observed at 401.5°C and 447°C.

[0044] <Saturation magnetization σ s and coercive force H c Measurements > The saturation magnetization σ of the submicron soft magnetic particles of Example 1 was measured using a complex permeability measurement method that combines a vibrating sample magnetometer (VSM) and a short-circuited microstrip line with a vector network analyzer. s (room temperature) and coercive force H c As a result, the saturation magnetization σ s is 74.58 emu / g, and the coercive force H c was 45.54 Oe.

[0045] <Complex permeability measurement> A resin composition prepared by mixing 50% by mass of the submicron soft magnetic particles of Example 1 and 50% by mass of an epoxy resin (model number: POS-000 Medium, manufactured by Teikoku Ink Co., Ltd.) was press-molded (pressure of 5 MPa, pressure time of 1 minute, pressure temperature of 120°C) into a sheet test piece (length 50 mm, width 50 mm). The real part μ' and imaginary part μ'' of magnetic permeability were measured at 0.1 GHz to 30 GHz for this sheet-like test piece using a complex permeability measurement method that combines a vibrating sample magnetometer (VSM) and a short-circuited microstrip line with a vector network analyzer. The measurement results are shown in FIG. 4. In FIG. 4, the upper curve indicates the real part μ' of magnetic permeability, and the lower curve indicates the imaginary part μ'' of magnetic permeability (the same applies to the following graphs showing the measurement results of complex permeability). As shown in FIG. 4, the real part μ' of magnetic permeability is 1.5, and the imaginary part μ'' of magnetic permeability has a broad peak from around 1 GHz, indicating that the material has excellent complex permeability.

[0046] The results of Example 1 show that the aqueous solution reduction reaction method using a metal salt aqueous solution with a pH of 13 or higher can produce particles with excellent soft magnetic properties as aggregates of submicron-sized (non-aggregating) spherical amorphous alloy microparticles consisting of Fe, Ni and B with a composition that roughly maintains the Fe and Ni content ratio in the metal salt aqueous solution, even at a low mixing temperature of 0°C.

[0047] [Comparative Example 1] The soft magnetic fine particles of Comparative Example 1 were produced by preparing an aqueous metal salt solution in the same manner as in Example 1, except that the pH of the aqueous metal salt solution (before mixing) in Example 1 was adjusted to 10. The Fe / Ni content ratio [C Fe :C Ni As a result, the Fe content C Fe and Ni content C Ni The content ratio [C Fe :C Ni ] is 3:7, and the ratio of Fe content to Ni content in the metal salt solution (5:5) is 3:7. Ni13, the soft magnetic particles of Comparative Example 1 were agglomerated particles of micron size, and it was found that submicron size particles could not be produced.

[0048] [Example 2] The submicron soft magnetic fine particles before heat treatment produced in Example 1 were heat treated under the following conditions to obtain submicron soft magnetic fine particles after heat treatment at each heat treatment temperature. (Heat treatment conditions) Heat treatment temperature: 400℃, 425℃, 450℃, 475℃ and 500℃ Heating rate: 200℃ / h Holding time: 1 hour after reaching the specified heat treatment temperature Heating atmosphere and pressure: Ar gas atmosphere, 4.0×10Pa

[0049] The average particle size and crystal structure of the submicron soft magnetic particles obtained after each heat treatment were evaluated in the same manner as in Example 1. As a result, the submicron soft magnetic particles after heat treatment at any of the heat treatment temperatures were an aggregate of spherical primary particles (non-aggregated), and had an average particle size D 50 The particles maintained a uniform particle size and an amorphous structure. In addition, the magnetic properties of the submicron soft magnetic particles after each heat treatment were measured in the same manner as in Example 1. The static magnetic properties (saturation magnetization σ s and coercive force H c ) are shown in Fig. 5, and the results of the dynamic magnetic properties (complex permeability) are shown in Fig. 6. For comparison, Fig. 5 shows the results of the submicron soft magnetic particles of Example 1 at the lower heat treatment temperature (annealing temperature) side. For comparison, Fig. 6 shows the results of the dynamic magnetic properties of the submicron soft magnetic particles produced in Example 1 before heat treatment as "as made." As shown in Figure 5, the saturation magnetization σ s increases with increasing heat treatment temperature, exceeding 80 emu / g. In particular, when the heat treatment temperature is 500°C, an excellent saturation magnetization σ of 92.9 emu / g is obtained. s On the other hand, the coercive force H cis decreased regardless of the heat treatment temperature, and shows high characteristics of less than 30 Oe. In particular, when the heat treatment temperature is 400° C., it shows excellent characteristics of 24.8 Oe. Moreover, as shown in Fig. 6, the real part of magnetic permeability μ' is improved from about 1.5 to 2-2.5 by heat treatment, regardless of the heat treatment temperature, showing high characteristics. Two peaks are observed in the imaginary part of magnetic permeability μ'', and the rise can be shifted to a high frequency band exceeding 1 GHz. The results of Example 2 show that by heat-treating submicron-sized microparticles produced by the aqueous solution reduction reaction method using a metal salt aqueous solution of pH 13 or higher, the soft magnetic properties can be further improved, and in particular, the excellent static magnetic properties can be enhanced while the dynamic magnetic properties can be improved to a high level (e.g., eddy current loss can be suppressed up to the high frequency band).

[0050] [Example 3] In Example 1, the content of iron (II) sulfate heptahydrate and the content of nickel sulfate hexahydrate in the metal salt aqueous solution were changed to molar ratios of 3:7, 4:6, 5:5, 6:4, 7:3 and 8:2, respectively. In the same manner as in Example 1, metal salt aqueous solutions were prepared and submicron soft magnetic fine particles before heat treatment were produced. The content ratio [C Fe :C M The average particle size was evaluated. The results are shown in Fig. 7. As shown in Fig. 7, even if the content ratio of Fe and Ni in the metal salt aqueous solution is changed, it is possible to produce, as submicron soft magnetic fine particles, an aggregate of spherical primary particles (non-aggregating) having a content ratio that approximately corresponds to the content ratio of Fe and Ni in the metal salt aqueous solution and an average particle size of submicron size of 150 to 350 nm. The magnetic properties of the submicron soft magnetic particles before each heat treatment were measured in the same manner as in Example 1. The results are shown in Figures 9 and 10. In Figures 9 and 10, the measurement results of the submicron soft magnetic particles before each heat treatment produced in Example 3 are indicated by "O" (as made). Saturation magnetization σ sAs shown by the circles in Fig. 9, the coercive force H c As shown by "◯" in FIG. 10, it can be seen that the value significantly decreases when the Fe content exceeds 0.6. The results of Example 3 show that in submicron soft magnetic particles containing Fe, Ni and B, even if the content ratio of Fe and Ni in the metal salt aqueous solution [Fe content: metal M content] is changed, it is possible to produce submicron soft magnetic particles having a composition that roughly maintains the content ratio of Fe and Ni in the metal salt aqueous solution, and that the magnetic properties (balance of magnetic properties, etc.) can be adjusted by changing the content ratio in the metal salt aqueous solution.

[0051] [Example 4] The submicron soft magnetic fine particles before heat treatment produced in Example 3 were each heat-treated under the following conditions to produce submicron soft magnetic fine particles after heat treatment. (Heat treatment conditions) Heat treatment temperature: 400℃ Heating rate: 200℃ / h Holding time: 1 hour after reaching the specified heat treatment temperature Heating atmosphere and pressure: Ar gas atmosphere, 4.0×10Pa

[0052] The submicron soft magnetic particles obtained after each heat treatment were photographed using a scanning electron microscope in the same manner as in Example 1. The images obtained are shown in Figure 8. As shown in Figure 8, it can be seen that the shape and average particle size of each submicron soft magnetic particle are maintained as those of the corresponding submicron soft magnetic particle before the heat treatment. In addition, the magnetic properties of the submicron soft magnetic particles after each heat treatment were measured in the same manner as in Example 1. The results are shown in Figures 9 to 11. In Figures 9 and 10, the measurement results of the submicron soft magnetic particles before each heat treatment produced in Example 4 are indicated by "▲" (annealed). Saturation magnetization σ s As shown by the "▲" in Figure 9, the coercive force H cAs shown by the "▲" in Figure 10, when the Fe content is 0.5 or less, it decreases or shows almost the same value, and when the Fe content exceeds 0.5, it increases. In this way, the content ratio can be appropriately set in consideration of the balance of static magnetic properties. As shown in Figure 11, it can be seen that the real part of magnetic permeability μ' increases as the Fe content increases. On the other hand, when the Fe content is 0.7 or less, the imaginary part of magnetic permeability μ'' shows two peaks, and the rise of these peaks shifts to the higher frequency side as the Fe content increases, and can be shifted up to a high frequency band exceeding 1 GHz.

[0053] [Example 5] <Preparation of metal salt aqueous solution> In a glass beaker, 10 g (0.2398 mol / L) of iron (II) sulfate heptahydrate, 10.1 g (0.2398 mol / L) of cobalt sulfate heptahydrate, and 5.4 g (0.3597 mol / L, 1.0 times the molar ratio of the total content of Fe and Ni) of glycine were added together with 150 mL of distilled water, and the mixture was stirred at room temperature (25°C) with a stirrer (80 rpm) until each component was dissolved. Sodium hydroxide was added to the resulting aqueous solution to adjust the pH to 13.5, preparing an aqueous metal salt solution. <Preparation of reducing agent aqueous solution> Into a glass beaker, 5.4 g (0.7135 mol / L) of sodium borohydride was placed together with 200 mL of distilled water, and the mixture was stirred at room temperature (25° C.) with a stirrer (stirring speed: 80 rpm) to prepare an aqueous reducing agent solution.

[0054] <Mixed> The metal salt aqueous solution and the reducing agent aqueous solution were each cooled to 0°C. In a nitrogen atmosphere, the entire amount of the aqueous reducing agent solution (internal temperature 0°C, the mixed amount of sodium borohydride relative to the total content of Fe content and Ni content was 1.49 times in molar ratio) was dropped at a dropwise rate of 200 mL / L into the entire amount of the aqueous metal salt solution (internal temperature 0°C) being stirred with a stirrer (stirring speed 80 rpm), and the mixed solution was stirred for 90 minutes, including the dropwise addition time, while continuing stirring. After stirring for 90 minutes, foaming from the mixture ceased and the reduction reaction was completed. After stirring for 90 minutes, the precipitated fine particles were collected by filtration, washed with distilled water, substituted with alcohol, and dried in an inert atmosphere of nitrogen gas to obtain submicron soft magnetic fine particles of Example 5.

[0055] The submicron soft magnetic particles of Example 5 thus produced were identified and evaluated in terms of composition, structure, magnetic properties, etc. in the same manner as in Example 1. As a result, the submicron soft magnetic particles of Example 5 were 39.4 Co 41.7 B 18.9 (The content of each atom is atm%, and the content ratio of Fe and Co is [C Fe :C Co ] is 4.9:5.1), and it is an aggregate of spherical primary particles (non-aggregated), with an average particle diameter D 50 The particle diameter was 350 nm, and the particle diameter distribution was narrow and uniform as shown in FIG. 12. The submicron soft magnetic particles had an amorphous structure, and the peak crystallization temperature by the above-mentioned TG-DTA was observed at 285° C. The saturation magnetization σ s is 147.5mu / g, and the coercive force H c was 125.1 Oe. The results of Example 5 show that even when Co is used as a metal M other than Fe, the aqueous solution reduction reaction method using a metal salt aqueous solution with a pH of 13 or higher can produce particles with excellent soft magnetic properties as an aggregate of submicron-sized (non-aggregating) spherical amorphous alloy microparticles having a uniform particle size and consisting of Fe, Co and B, with a composition that roughly maintains the Fe and Co content ratio in the metal salt aqueous solution, even at a low mixing temperature of 0°C.

Claims

1. Submicron soft magnetic fine particles containing Fe, metal M other than Fe, and B.

2. 2. The submicron soft magnetic particles according to claim 1, wherein said metal M comprises at least one selected from Ni, Co, Zn, Al, Mn and Cr.

3. The Fe content C Fe (atm%) and the content C of the metal M M (atm%) and the content ratio [C Fe :C M 2. The submicron soft magnetic particles according to claim 1, wherein the ratio of .alpha.-to-.alpha. / .alpha. is 3:7 to 8:

2.

4. A method for producing submicron soft magnetic particles containing Fe, a metal other than Fe, M, and B, comprising the steps of: A production method comprising mixing an aqueous solution of a metal salt containing an Fe salt, a metal salt other than an Fe salt, and a complexing agent and having a pH of 13 or more with an aqueous solution of a reducing agent containing a B-based reducing agent.

5. The method according to claim 4 , wherein the mixing is carried out under non-heating conditions.

6. The method of claim 4 , wherein the complexing agent comprises glycine.

7. The method according to claim 4 , further comprising heat treating the fine particles obtained by the mixing.

8. A soft magnetic material comprising the submicron soft magnetic particles according to any one of claims 1 to 3.

9. A soft magnetic material comprising the submicron soft magnetic particles according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Reflux device for exhaust gas of engine

    JP1978082923A